Agency theory in a nonprofit organization - Ecco, Ivan Luiz (2010)
The aim of this paper is to analyze, based on the agency theory, the existence of agency conflicts in management by results in a professional education nonprofit organization. For the program, the case study method was used in a nonprofit professional education organization, located in the state of Santa Catarina. The study examined the contract between the Headquarters of the Organization (which represents in this study, according to theory of agency, the principal) and its School Units (representing, the agents) to accomplish goals. The results show that the asymmetry of information and organizational culture are factors that contribute to the problem of agency and the determination of an optimal contract should take into consideration such situations. The main conclusion is that agency problems are also present in nonprofit organizations, even when an instrument for the management by results is implemented.